144 A druggable inhibitor of cardiac hypertrophy identified through an innovative chemical library screen. (9th June 2011) - Leisa, R Abou; Mohamed, T M A; Oceandy, D; Prehar, S; Zi, M; Baudoin, F; Neyses, L; Cartwright, E J
Abstract : Cardiac hypertrophy is a prerequisite for the development of heart failure. It currently affects almost one million people in the UK. Few effective anti-hypertrophic agents with druggable properties have been identified. Recently, our group showed that plasma membrane calcium ATPase isoform 4 (PMCA4) knockout mice showed a reduced response to hypertrophic stress prompting us to hypothesise that a novel PMCA4 specific inhibitor would modify the development of cardiac hypertrophy. A library of 1280 medically optimised compounds was screened using a novel in vitro assay which measures the Ca2+ dependent ATPase activity of PMCA4. The compound AP2 was identified, which inhibited PMCA4 activity with high affinity (IC50 =300 nM) but not other PMCAs (PMCA1, PMCA2 and PMCA3) or related ATPases which are expressed in the heart including the sarcoplasmic reticulum calcium ATPase and Na/K ATPase. In isolated neonatal rat cardiomyocytes (NRCM), AP2 showed dose dependent inhibition of phenylephrine-induced hypertrophy, indicated by an 85% reduction in cell surface area as well as in BNP activity. In vivo studies showed that AP2 (5 mg/kg body weight/day IP) significantly reduced pressure-overload induced hypertrophy following 2 weeks transverse aortic constriction (TAC) (heart weight/tibia length (mg/mm): sham, 5.5±0.3, vehicle treated TAC mice, 8.7 ±0.2, AP2 treated TAC mice, 7.0 ±0.5, n=10 in each group, p<0.01). AP2 treated TAC mice showed a significant reduction in the cardiomyocyte cross sectional area (sham, 267±3.4 μm 2, vehicle treated TAC mice, 480±5.8 μm 2, AP2 treated TAC mice, 319±3.9 μm 2 ). A significant reduction in the expression of the hypertrophic marker ANP and BNP and in the percentage of fibrosis was also observed in these mice compared with vehicle treated TAC mice. AP2 treatment led to a significant reduction in the expression of the bona fide calcineurin target RCAN1.4 and a reduction in the NFAT phosphorylation level in vivo and the NFAT transcriptional activity in vitro. In conclusion, we have identified AP2 as a novel PMCA4 specific inhibitor and shown its potential to modify the development of cardiac hypertrophy likely through inhibition of calcineurin/NFAT signalling. This compound has drug-like properties and thus lays the basis for a novel approach for treating cardiac hypertrophy and failure through PMCA4 inhibition.